The little drummer boy [videorecording (DVD)] - Garson, Greer, 1904-1996; Ferrer, José, 1912-1992; Rankin, Arthur, Jr; Bass, Jules; Davis, Katherine, 1892-1980 (Classic Media ; Distributed by Vivendi Entertainment, 2011)
An orphaned drummer boy witnesses the birth of baby Jesus. Having no gift for him, he gives the only thing he has: a song.